2001
DOI: 10.1046/j.0263-4929.2001.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastability of granulites and processes of eclogitisation in the UHP region of western Norway

Abstract: The Flatraket Complex, a granulite facies low strain enclave within the Western Gneiss Region, provides an excellent example of metastability of plagioclase‐bearing assemblages under eclogite facies conditions. Coesite eclogites are found <200 m structurally above and <1 km below the Flatraket Complex, and are separated from it by amphibolite facies gneisses related to pervasive late‐orogenic deformation and overprinting. Granulites within the Flatraket Complex equilibrated at 9–11 kbar, 700–800°C. These preda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 38 publications
(81 reference statements)
2
103
1
Order By: Relevance
“…Amphibolite-facies metabasites occur together with mafic granulites and HP-to UHP-eclogites on km to cm scales (e.g. Austrheim and Engvik, 1997;Krabbendam et al, 2000;Wain et al, 2001). It has been shown that variability in the preserved metamorphic signature is due to heterogeneous strain and fluid ingress along the rocks' P,T evolution.…”
Section: The Western Gneiss Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphibolite-facies metabasites occur together with mafic granulites and HP-to UHP-eclogites on km to cm scales (e.g. Austrheim and Engvik, 1997;Krabbendam et al, 2000;Wain et al, 2001). It has been shown that variability in the preserved metamorphic signature is due to heterogeneous strain and fluid ingress along the rocks' P,T evolution.…”
Section: The Western Gneiss Regionmentioning
confidence: 99%
“…It has been shown that variability in the preserved metamorphic signature is due to heterogeneous strain and fluid ingress along the rocks' P,T evolution. Strain and fluid availability imposes kinetic control on rock and mineral reactivity, so that in absence of these factors assemblages can be metastably preserved even through episodes of extreme overstepping of equilibrium P,T conditions (Wayte et al, 1989;Austrheim, 1998;Krabbendam et al, 2000;Wain et al, 2001). …”
Section: The Western Gneiss Regionmentioning
confidence: 99%
“…The eclogites make up c. 5% of the Flatraket area and are partially retrogressed to amphibolite-facies assemblages. The granulite is also strongly affected by amphibolite-facies retrogression (Krabbendam & Wain, 1997;Wain et al, 2001). …”
Section: Flatraketmentioning
confidence: 99%
“…Evidence from numerous localities, including the Bergen Arcs and Western Gneiss Region in Norway, and the Western Alps, suggests that granulite-facies rocks can persist metastably through a subduction-exhumation cycle so long as they remain dry and/or undeformed (Wain et al, 2001, and references therein). What is less clear is whether "wetter" continental crust behaves equally metastably under subduction conditions.…”
Section: Internal Driver Of Exhumation: Buoyancymentioning
confidence: 99%